Exceptionally active iridium evolved from a pseudo-cubic perovskite for oxygen evolution in acid - Yubo Chen (Nature Portfolio, 2019)
While water splitting could provide a green means to store energy, there are few materials that can sustain high water oxidation half-reaction rates in acidic electrolytes. Here, authors design a perovskite oxide that generates high performance under-coordinated iridium sites during electrocatalysis.